Study on Preparation Method of Terminal Blend Rubberized Asphalt Binder - Xie, Juan; Zhang, Yongning; Yang, Yueming (Frontiers in Materials, 2020)
Terminal Blend (TB) asphalt rubber is prepared by being sheared with high speed for a long time a high temperature and has good low temperature performance and anti-fatigue performance. But due to the aging of asphalt and desulfurization and degradation of crumb rubber, the high temperature performance of TB is not ideal. In order to propose an effective way to solve this problem and improve the high temperature performance, a series of TB-B and TB-C asphalt were prepared with crumb rubber by changing dosage and preparation temperature in nitrogen environment and soluble crumb rubber in atmospheric environment, respectively. As a comparison group, TB-A asphalt was prepared using crumb rubber under atmospheric environment. Dynamic shear rheometer (DSR) and binding beam rheometer (BBR) were used to investigate the rheological characteristics, polymer segregation experiment was performed to evaluate the storage stability, and Fourier Transform Infrared (FTIR) spectroscopy and thermogravimetric analysis were carried out to explore the aging degree of asphalt. TB-A had good storage stability but was brittle due to serious asphalt aging during preparation, and its high and low temperature performance were not good. The introduction of nitrogen could effectively decline aging degree and guaranteed TB-B best comprehensive performance among these three kinds of modified asphalt. Soluble crumb rubber was obtained by pretreating crumb rubber and making it desulfurize and degrade, which reduced the preparation and consequently inhibit the occurrence of aging. The high and low temperature properties of TB-C met specification, but storage stability was not insufficient when crumb rubber content was more than 15%. Overall, both preparation in nitrogen environment with conventional crumb rubber and preparation in atmospheric environment with soluble crumb rubber can effectively alleviate the aging degree of TB asphalt.